KEBIJAKAN PERIZINAN LINGKUNGAN HIDUP DI DAERAH ISTIMEWA YOGYAKARTA - H. Rhiti; Y. Sri Pudyatmoko (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractIn DIY the environmental permit is recognized as an istrument for preventing the environmental problems. Local Government policies related to environmental permits are: the harmonization of economic interests with local wisdom and the environment; the interconnection between environmental permits and spatialplanning; the environmental permit as a requirement for the nuisance permit and building permit; the application of SPPL (statement letter to manage the environment) for small lactivities. According to local governments, the policies are appropriate to protect the environment.IntisariDi DIY perizinan lingkungan diakui sebagai instrumen untuk mencegah timbulnya masalah lingkungan hidup. Kebijakan Pemerintah Daerah terkait perizinan lingkungan dilakukan dengan: harmonisasi kepentingan ekonomi, muatan lokal dan lingkungan; mengaitkan perizinan lingkungan dan RTRW; menjadikan Izin Lingkungan sebagai syarat bagi Izin Gangguan dan IMB; dan penerapan SPPL bagi kegiatan mikro dan kecil. Kebijakan-kebijakan tesebut dianggap oleh Pemerintah Daerah sebagai cukup tepat bagi pelestarian fungsi lingkungan hidup di daerah.